Coping With Health Threats: The Costs and Benefits of Managing Emotions. (July 2021) - Smith, Angela M.; Willroth, Emily C.; Gatchpazian, Arasteh; Shallcross, Amanda J.; Feinberg, Matthew; Ford, Brett Q.
How people respond to health threats can influence their own health and, when people are facing communal risks, even their community's health. We propose that people commonly respond to health threats by managing their emotions with cognitive strategies such as reappraisal, which can reduce fear and protect mental health. However, because fear can also motivate health behaviors, reducing fear may also jeopardize health behaviors. In two diverse U.S. samples ( N = 1, 241) tracked across 3 months, sequential and cross-lagged panel mediation models indicated that reappraisal predicted lower fear about an ongoing health threat (COVID-19) and, in turn, better mental health but fewer recommended physical health behaviors. This trade-off was not inevitable, however: The use of reappraisal to increase socially oriented positive emotions predicted better mental health without jeopardizing physical health behaviors. Examining the costs and benefits of how people cope with health threats is essential for promoting better health outcomes for individuals and communities.